2022
DOI: 10.1002/nop2.1561
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relationship between lateral violence and nursing professionalism through the mediating effect of professional identity: A cross‐sectional questionnaire study

Abstract: Aim This study aimed to investigate the prevalence of lateral violence (LV) experienced by nursing students during their internship, explore the difference between professional identity and professionalism among nursing students who had or had not experienced LV and analyse the mediating effect of professional identity on the relationship between LV and professionalism. Design A cross‐sectional survey was used. Methods An online anonymous survey was distributed to nursing students (N = 298) in Jiangsu province… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 60 publications
0
5
0
2
Order By: Relevance
“…Our findings revealed that nursing image and nursing professionalism were positively associated with career preparation behavior. This result was consistent and nursing students had high nursing professional values before clinical practice, but then they were influenced by negative factors from witnessing and experiencing the performance of their duties and the roles of nurses in hospitals in practice [26][27][28]. Major emergencies affect the perspective of students on the meaning of work and life, thereby damaging the impulse to seek out meaningful pursuits [26].…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Our findings revealed that nursing image and nursing professionalism were positively associated with career preparation behavior. This result was consistent and nursing students had high nursing professional values before clinical practice, but then they were influenced by negative factors from witnessing and experiencing the performance of their duties and the roles of nurses in hospitals in practice [26][27][28]. Major emergencies affect the perspective of students on the meaning of work and life, thereby damaging the impulse to seek out meaningful pursuits [26].…”
Section: Discussionmentioning
confidence: 74%
“…A previous study revealed that professionalism was influenced by self-efficacy [ 9 , 21 , 27 , 39 ]. In addition, self-efficacy plays an important role in professionalism [ 28 ] and it was found that as the strongest predictor, it also influenced the career preparation of nursing students [ 30 ]. The COVID-19 pandemic highlighted the flaws in healthcare systems, which highlights the critical need for all governments to make significant investments in nursing in order to bring about such profound changes [ 16 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Professional identity Nursing professional identity refers to nurses acknowledging their work and affirming their self-worth [40]. This study defines professional identity as a gradual "process" and a "state.…”
Section: "Sometimes Friends and Relatives Ask Me About Hospitalizatio...mentioning
confidence: 99%
“…Having a good professional identity can help nursing students build the core competitiveness [ 18 ], including their innovative ability [ 19 ]. Positive professional identity can enhance the nurses' care quality [ 15 ] and adjust the role pressure of nursing students [ 20 ]; moreover, it can help nurse students stay in the nursing profession after graduation [ 21 , 22 ], reduce their intention to quit [ 23 , 24 ], and increase their job satisfaction [ 25 ]. During the final-year students’ internship, nursing students can put theory into practice [ 26 ], nursing educators play an important on guide students found professional values and build professional identity [ 27 ].…”
Section: Introductionmentioning
confidence: 99%